Enhancing STEM Interest through Robotics Education in a Malaysian Primary School - Yusrina, Yusof; Oswald Timothy, Edward; Kamaru Adzha, Kadiran; Ezril Hisham, Mat Saat; Arni Munira, Markom (INTI International University, 2024)
This study investigates the impact of robotics education on enhancing STEM interest among students in a Malaysian primary school. As Malaysia aims to become a technological innovation hub, fostering STEM interest in youth is crucial. Traditional education methods focusing on rote memorization contribute to a significant gap in practical STEM skills, especially in robotics. This study addresses these challenges through a mixed-methods approach, conducting a "Robotic Day" workshop at SJK(C) Pei Chih for 30 Standard 5 students. Pre- and post-workshop surveys and in-depth interviews assessed changes in students' STEM knowledge, attitudes, and interests. Results showed a significant increase in students' understanding and enthusiasm for STEM, with the proportion of participants demonstrating good and very good levels of knowledge rising from 10.3% to 69.2%. Additionally, the percentage of students with low interest in STEM dropped from 44.8% to 7.6% post-workshop. These findings underscore the effectiveness of hands-on robotics education in bridging educational gaps, fostering critical thinking, and nurturing future STEM professionals. This study supports Sustainable Development Goal 4, promoting inclusive and equitable quality education.